2015
DOI: 10.1016/j.jpain.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Age Group Comparisons of TENS Response Among Individuals With Chronic Axial Low Back Pain

Abstract: Chronic low back pain (CLBP) is a highly prevalent and disabling musculoskeletal pain condition among older adults. Transcutaneous electrical nerve stimulation (TENS) is commonly used to treat CLBP, however, TENS response for older adults compared to younger adults is untested. In a dose-response study stratified by age, sixty participants with axial CLBP (20 young, 20 middle-aged, 20 older) received four 20-minute sessions of high frequency, high intensity TENS over a two to three-week period in a laboratory-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 68 publications
0
22
1
4
Order By: Relevance
“…Second, measures were collected following TENS or TENS placebo application. Evidence suggests that pain reduction from TENS is episodic and may be better detected during delivery of the electric current or immediately after . However, the pain assessment technique that we utilized is ecologically valid from the participant's perspective, in that the overall success of a treatment is determined after the treatment is administered, not during.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, measures were collected following TENS or TENS placebo application. Evidence suggests that pain reduction from TENS is episodic and may be better detected during delivery of the electric current or immediately after . However, the pain assessment technique that we utilized is ecologically valid from the participant's perspective, in that the overall success of a treatment is determined after the treatment is administered, not during.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that pain reduction from TENS is episodic and may be better detected during delivery of the electric current or immediately after. [84][85][86] However, the pain assessment technique that we utilized is ecologically valid from the participant's perspective, in that the overall success of a treatment is determined after the treatment is administered, not during. Third, because there are no universally accepted dosing parameters and studies often use a range of dosing applications, our findings can only be compared to prior studies using similar conventional TENS parameters (ie, short pulse width and strong, but comfortable, intensities).…”
Section: Limitationsmentioning
confidence: 99%
“…This could have influenced TENS efficacy since it was shown that the intensity of an efficacious stimulation differed according to patient's age, namely 25.3 mA in the elderly patients vs 7.9 mA and 9.6 mA in the younger and middle-aged patients, respectively. [33] Intensity modifications were not performed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…3 Várias estratégias de tratamento vem sendo utilizadas como programas de exercícios com controle motor dos músculos do tronco através de exercícios de estabilização do Core, exercícios de fortalecimento e alongamentos. 4 Na prática fisioterapêutica, diferentes agentes eletrofísicos são utilizados para obter alívio da dor relacionado aos problemas musculoesqueléticos, a fim de complementar outras intervenções terapêuticas, particularmente a realização de exercícios corretivos. 5 Em indivíduos com dor lombar, deuma forma geral, o alívio imediato da dor aguda durante as primeiras sessões de fisioterapia fornece o terreno adequado para o início dos exercícios.…”
Section: Introductionunclassified
“…5 A TENS é uma técnica amplamente utilizada dentro da eletroterapia, sendo considerada um tratamento coadjuvante simples e seguro, podendo ser efetiva para manejo da dor lombar de diversas causas, mecânicas ou radiculares. 4 A estimulação elétrica nervosa transcutânea (TENS) é uma das modalidades mais comumente usadas, com evidência moderada a forte de sua capacidade de modular a dor em diferentes condições de dor. 5 Foi demonstrado que a TENS pode diminuir a dor durante, logo após e por um intervalo de tempo determinado após aplicação nos tecidos moles lesionados 5 .…”
Section: Introductionunclassified